2022
DOI: 10.55563/clinexprheumatol/r6her6
|View full text |Cite
|
Sign up to set email alerts
|

The clinical features, image findings and risk factors of vena cava syndrome in Behçet's syndrome

Abstract: Objective To investigate the clinical features, image findings, and potential risk factors of vena cava syndrome (VCS) inBehçet's syndrome (BS). MethodsWe conducted a case-control study in our BS registry database from 2012 to 2021. Fifty-five BS patients with VCS were enrolled in the case group, and two BS patients without VCS were selected as controls for each VCS case using risk-set-sampling. Multivariable logistic regression was used to detect the risk factors of VCS, and the outcome of these patients was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…CTPA can detect all the main features of BD, especially for aneurysms, showing a relationship with surrounding structures and giving indications for surgical approach [ 19 , 24 , 25 , 26 ]. Zhou, J., et al reported that spectral CT is better in detecting thrombosis at a low energy level of 40 keV using virtual monoenergetic imaging than conventional imaging at 120 kV [ 27 ]. Angiography is not recommended in patients with BD because of the increased risk of aneurysm formation at the puncture site and venous thrombosis after the injection of the contrast material [ 18 ].…”
Section: Imaging Approach To Thoracic Involvement In Behcet’s Diseasementioning
confidence: 99%
“…CTPA can detect all the main features of BD, especially for aneurysms, showing a relationship with surrounding structures and giving indications for surgical approach [ 19 , 24 , 25 , 26 ]. Zhou, J., et al reported that spectral CT is better in detecting thrombosis at a low energy level of 40 keV using virtual monoenergetic imaging than conventional imaging at 120 kV [ 27 ]. Angiography is not recommended in patients with BD because of the increased risk of aneurysm formation at the puncture site and venous thrombosis after the injection of the contrast material [ 18 ].…”
Section: Imaging Approach To Thoracic Involvement In Behcet’s Diseasementioning
confidence: 99%
“…Wu and Lulu described a patient who presented with ICT attached to the pulmonary valve and on the apex of the left ventricle (60). A case control study showed that male gender, young age of onset, high acute phase response and positive pathergy reaction were associated with vena cava superior (VCS) thrombosis and patients with VCS thrombosis had a better survival and lower relapse rates than those with arterial involvement (61). A comparison of two cohorts from Turkey (n=160) and France (n=131) revealed that Turkish patients were more likely to have a family history, HLA-B51 and pathergy positivity whereas, French patients tend to have more neurological involvement and higher recurrence risk (HR=1.64; 95%CI 1.1-2.44, p=0.014) (62).…”
Section: Vascular Involvementmentioning
confidence: 99%
“…• Sensitivity and specificity of the pathergy test improve with the addition of pneumococcal vaccine (44). • Patients with VCS thrombosis have a better survival and lower relapse rates compared to those with arterial involvement (61). • The prevalence of AA amyloidosis has decreased over the years (77).…”
Section: Take Home Messagesmentioning
confidence: 99%